PENINGKATAN KARAKTER DAN HASIL BELAJAR BIOLOGI SISWA SMP MELALUI MODEL PEMBELAJARAN THINK TALK WRITE DIPADU TALKING STICK - Lidya Yanuarta (Jurnal Pendidikan Biologi, 2015)
Observation result in SMPN 2 Kalisat-Jember showed the students character and  achievement in class VII-E still low. This problem can be fixed with the implementation Think Talk Write combined with Talking Stick. The purpose of this research was to increase  students character, achievement, and completeness of student achievement. This research was Classroom Action Research. Result of this research, there was increasing character from first cycle until second cycle.  Inquiring sense character increased to BT (Belum Terlihat) or (Not Appeared) with percentage 67.10%. Then discipline character increased on MB (Mulai Berkembang) or (Start Growing) with percentage 51,31%. Then responsibility character increased on MK (Menjadi Karakter) or (Start Consistent) with percentage 47,36%. The increase of average achievement was 77,1 and classical thoroughness in cognitive aspect was increased become 78,94%. It concluded that cooperative learning model of Think Talk Write with Talking Stick can increased students character, achievement, and completeness of students achievement in class VII E SMP Negeri 2 Kalisat Jember.Keywords: think talk write, talking stick, students character, achievement